Specialist investigation of obscure gastrointestinal bleeding. Issue 1 (January 1987) - Thompson, J N; Salem, R R; Hemingway, A P; Rees, H C; Hodgson, H J; Wood, C B; Allison, D J; Spencer, J
Abstract : The investigation and treatment of 131 patients with 'obscure' gastrointestinal bleeding has been reviewed. One hundred and six patients were assessed electively for recurrent haemorrhage, 25 presented as emergencies. The major presenting feature was melaena (55 patients), anaemia (35), rectal bleeding (34), haematemesis (six) and ileostomy bleeding (one). The lesions responsible for haemorrhage were colonic angiodysplasia (52 patients), small bowel vascular anomalies (16), Meckel's diverticula (nine), small bowel smooth muscle tumours (seven), gastric vascular anomalies (four), chronic pancreatitis (three), colonic diverticular disease (three) and 16 other miscellaneous lesions. No lesion was found in 21 cases. Lesions were first shown by visceral angiography (69 patients), at laparotomy (23), on endoscopy (11), on gastrointestinal contrast radiological studies (four), and at ERCP (three). Lesions which were undetectable at operation increased markedly with age (p less than 0.0001). Expert visceral angiography is strongly recommended before surgery in patients over 45 years of age and after laparotomy when no cause has been found. Exploratory laparotomy is recommended at an early stage for younger patients, and for older patients after non-diagnostic angiography.